The Role of Teachers in Overcoming Bullying Behavior in Students to Form the Social Character of Students at MI Nurul Huda Krenceng, Nglegok District, Blitar Regency - Dahana, Eva Oktariani; Izzati, Ainina Fitriyatul; Purwowidodo, Agus; Huda, Muh. Nurul (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2026)
Bullying is an aggressive act carried out repeatedly by an individual or group with more power or influence against another weaker individual, with the aim of hurting, intimidating, or dominating them physically, verbally, psychologically, or socially. The role of teachers in the context of modern education is not limited to conveying knowledge, but extends to being facilitators, motivators, evaluators, and role models in the development of students' character. This research uses a qualitative approach with a post-positivistic paradigm and is a case study. Data collection was conducted through in-depth interviews and participant observation, and data analysis was conducted using the Milles, Huberman, and Saldana model. Result are the role of teachers is not only as educators but also as managers of the school's social environment. Therefore, it is necessary to improve teachers' understanding of various forms of bullying, particularly cyberbullying, which is difficult to monitor. Teachers need to be equipped with specialized training and supported by clear and targeted school policies. Schools also need to involve all elements, including students and parents, in bullying prevention programs. A collaborative approach is considered essential for creating a safe and comfortable learning environment. Strengthening the role of teachers as key figures in bullying prevention needs to be a primary focus. Support from schools and educational institutions is needed in the form of professional development, reflection spaces, and psychological counseling. With this support, teachers can be better prepared to face social challenges in the classroom.